A dialética da desalienação: uma leitura marxista do romance caim, de José Saramago - Santos, José Diego Cirne (2013)
The writer José Saramago published his last novel, Caim, in 2009. This narrative exemplifies the books of the Portuguese writer who has as thematic axis the religion, connected, in this case to the Judeo imaginative of the Old Testament. The aesthetical construction of his work has the logical purpose of making a critical review of the biblical episodes that re-build, after all when casting as protagonist in his plot the character Caim , who in his wandering destiny, sentenced after his brother s murder, visits endless episodes of tradition of the Old Testament, in which encounter several god s oppressors, which make him rebel against the divine tyranny. This fictional procedure is stylized through an omniscient narrator that launch constantly over the mythical plot that rebuild critical-ironic comments, modern linguistic-allegorical suggestions, meta-linguistic digressions and sociological connotations of Marxist impressions. This constant intrusion in the enunciation plan about the declared plot is a diegetic transgression that putting in evidence the judgments of value of this contemporary narrator, possible intends to arouse in the reader a depreciative sense about the Judeo-Christian religion contradictions. Therefore, with the purpose of contributing with the critical wealth about the author and the work in question e promoting an interpretative quest of academic relevance about the textual implications of stylistic use of this resource, this dissertative work has as a study proposal, the analysis of the obtrusion of the voice announcer in this parodistic plot, starring by the shock between the first humankind murderer and the Israel sovereign divinity, through the basement in theoretical-critical that traverse about José Saramago s work, the narrator aesthetical positioning in the Romanesque narratives, the literary archetypes and the Marxist conceptualizations upon the religious ideology, class struggle and alienation.